In vitro evidences of mycoparasitism of the ectomycorrhizal fungus Pisolithus tinctorius by Hypholoma fasciculare - Baptista, Paula (2006)
In the northeast of Portugal macrofungi community associated to chestnut tree (Castanea sativa Mill.) is rich and diversified. Among fungal species, Pisolithus tinctorius and Hypholoma fasciculare are common in this habitat. In vitro interaction between P. tinctorius and H. fasciculare was investigated, to ascertain the potential mycoparasitic capabilities of H. fasciculare in the growth suppression of ectomycorrhizal P. tinctorius. The results show that in co-culture, the growth of P. tinctorius was drastically inhibited by H. fasciculare. Preliminary studies seem to evidence P. tinctorius hyphal injury and stress response in the contact zone between both mycelia. As the chestnut inoculation with these fungi showed higher hyphal adhesion of H. fasciculare to the roots in comparison with P. tinctorius adhesion, mycoparasitism of P. tinctorius by H. fasciculare could bring serious consequences to chestnut orchards, even more because the continuous contact of H. fasciculare with chestnut roots seems to promote the destruction of vascular root system. In addition, as both fungi exhibit high adhesion capacity to chestnut roots, the involvement of hydrophobins, proteins reported to be involved in the fungus adhesion to other organisms, is being studied by expression analysis in P. tinctorius or H. fasciculare after being in contact with C. sativa roots.